Roitt's Essential Immunology - Roitt, Ivan (BLACKWELL SCIENCE, 1997)
Roitt's Essential Immunology clearly outdistances other textbooks in the area by its scope, its organisation, its clarity and its ability to convey a carefully balanced and up-to-date view of immunology.